2006
DOI: 10.1021/ic051679g
|View full text |Cite
|
Sign up to set email alerts
|

Production and Reactions of Organic-Soluble Lanthanide Complexes of the Monolacunary Dawson [α1-P2W17O61]10-Polyoxotungstate

Abstract: The incorporation of lanthanides into polyoxometalates provides entry to new classes of potentially useful materials that combine the intrinsic properties of both constituents. To utilize the [alpha1-Ln(H2O)4P2W17O61]7- species in applications of catalysis and development of luminescent materials, the chemistry of this family of lanthanide polyoxometalates in organic solvents has been developed. Organic-soluble polyoxometalate-lanthanide complexes TBA5H2[alpha1-Ln(H2O)4P2W17O61] (Ln = La(III), Sm(III), Eu(III)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 58 publications
5
69
0
Order By: Relevance
“…We were able to reuse the same catalyst up to ten times with no loss in yield. The following experimental facts made us confident that there had been no leaching of Yb 3+ : 1) our initial work bears out the decomplexation of Yb 3+ from the POM upon precipitation; [30] 2) Yb 3+ is paramagnetic and would influence the NMR spectra of the filtrate, which was not the case (no paramagnetic shift or line broadening); 3) after removal of the POM-Ln complex, the supernatant showed no catalytic activity.…”
Section: Methodsmentioning
confidence: 83%
See 1 more Smart Citation
“…We were able to reuse the same catalyst up to ten times with no loss in yield. The following experimental facts made us confident that there had been no leaching of Yb 3+ : 1) our initial work bears out the decomplexation of Yb 3+ from the POM upon precipitation; [30] 2) Yb 3+ is paramagnetic and would influence the NMR spectra of the filtrate, which was not the case (no paramagnetic shift or line broadening); 3) after removal of the POM-Ln complex, the supernatant showed no catalytic activity.…”
Section: Methodsmentioning
confidence: 83%
“…We thus switched to complexes that are soluble in organic solvents, [30] especially acetonitrile, and were able to isolate b-amino ketones 1 a-e, thus proving the catalytic activity of the POM-Ln complexes, although the reaction times were generally longer than those observed with the corresponding lanthanide triflates (two days vs. a few hours). This was expected considering the decreased Lewis acidity of the lanthanides when complexed to the monovacant POM ligand.…”
mentioning
confidence: 87%
“…Dimerization in the solid state of the complex {a 1 -La} 2 occurs through a capping W=O site. [44] Chiral differentiation Amino acids as ligands: Pope et al reported differentiation of the 31 P NMR signals of {a 1 -Ce} by addition of enantiomerically pure amino acids, in particular l-proline. [33] We decided to follow this approach and recorded the spectra of a series of complexes {a 1 The largest chiral differentiation is obtained for {a 1 -Yb}, which may be attributable to larger paramagnetic shift of the complex.…”
Section: Resultsmentioning
confidence: 99%
“…[3] Polyoxometalate clusters cover an enormous size range and comprise conserved/transferable building blocks; it is this feature that means they hold considerable promise for the controlled assembly of large nanostructures and framework materials. [4] The synthesis of organic-inorganic hybrid POMs has attracted widespread attention in the domain of materials science since the nanoscale clusters, which are highly anionic, are perfect scaffolds for the development of hybrid assemblies, though direct covalent modification of POMs is rare and only a few POM clusters including [Mo 6 O 19 ] 2À , [5] a 1 /a 2 -[P 2 W 17 O 61 ] 10À , [6][7] some organophosphoryl [8] and organosilyl [9] derivatives of lacunary POM clusters have been covalently functionalized to date. [10] As these hybrid materials will combine not only the advantages of or-A C H T U N G T R E N N U N G ganic components and inorganic clusters, but also the close interaction and synergistic effect between them, it is of great interest to develop such organic-inorganic hybrids through covalent functionalization.…”
Section: Introductionmentioning
confidence: 99%